Significance of Exercise‐Related Ventricular Arrhythmias in Patients With Brugada Syndrome - Morita, Hiroshi (J Am Heart Assoc, 2020)
BACKGROUND: Sinus tachycardia during exercise attenuates ST‐segment elevation in patients with Brugada syndrome, whereas ST‐segment augmentation after an exercise test is a high‐risk sign. Some patients have premature ventricular contractions (PVCs) related to exercise, but the significance of exercise‐related PVCs in patients with Brugada syndrome is still unknown. The objective of this study was to determine the significance of exercise‐related PVCs for predicting occurrence of ventricular fibrillation (VF) in patients with Brugada syndrome. METHODS AND RESULTS: The subjects were 307 patients with Brugada syndrome who performed a treadmill exercise test. We evaluated the occurrence of PVCs at rest, during exercise and at the peak of exercise, and during recovery after exercise (0–5 minutes). We followed the patients for 92±68 months and evaluated the occurrence of VF. PVCs occurred in 82 patients (27%) at the time of treadmill exercise test: PVCs appeared at rest in 14 patients (4%), during exercise in 60 patients (20%), immediately after exercise (0–1.5 minutes) in 28 patients (9%), early after exercise (1.5–3 minutes) in 18 patients (6%), and late after exercise (3–5 minutes) in 12 patients (4%). Thirty patients experienced VF during follow‐up. Multivariable analysis including symptoms, spontaneous type 1 ECG, and PVCs in the early recovery phase showed that these factors were independently associated with VF events during follow‐up. CONCLUSIONS: PVCs early after an exercise test are associated with future occurrence of VF events. Rebound of vagal nerve activity at the early recovery phase would promote ST‐segment augmentation and PVCs in high‐risk patients with Brugada syndrome.